WHEAT ANTIMICROBIAL PEPTIDES - T. I. Odintsova; T. V. Korostyleva; L. L. Utkina; Ya. A. Andreev; A. A. Slavokhotova; E. A. Istomina; V. A. Pukhal’skii; T. A. Egorov (Вавиловский журнал генетики и селекции)
Antimicrobial peptides (AMPs) are low-molecular-weight defense polypeptides, produced in all living organisms either constitutively or upon perception of signals from pathogenic microorganisms. They are important components of the immune system in both animals and plants. AMPs differ in structure and mode of action. Most of them belong to cysteine-rich peptides; their molecules contain even numbers of cysteine residues involved in the formation of disulphide bonds, which stabilize the peptide structure. A number of families of plant AMPs have been isolated on the base of amino acid sequence similarity and 3D structure. Plant AMP genes can be used in the engineering of pest resistance in crops and development of novel antibiotics and antimycotics. We provide a concise review of properties and gene structures of major AMP families discovered by the authors in Triticum kiharae seeds, including glycine-rich peptides, defensins, hevein-like peptides and the so-called 4-Cys peptides.